The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1097/md.0000000000016713
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of nutritional status and prognostic impact assessed by the prognostic nutritional index in children with chronic kidney disease

Abstract: To evaluate the nutritional status of children with chronic kidney disease (CKD) before dialysis via a series of indexes, and investigate the prognostic impact of nutritional status in these patients assessed by the Prognostic Nutritional Index (PNI). Fifty-four children with CKD before dialysis were enrolled in this study. The nutritional status was evaluated by different indexes, including dietary intake, anthropometry data and biochemical parameters. Additionally, PNI is calculated as 10 × serum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 25 publications
2
36
1
Order By: Relevance
“…After Onodera suggested the cutoff of PNI value as 45 13 , this is frequently used 17 , 38 . However, the researchers chose several cutoff levels according to study design, such as median, tertile, or ROC analysis 15 , 18 , 20 , 39 . In previous studies, the PNI cut-off value for defining undernutrition varied between 45 and 50.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After Onodera suggested the cutoff of PNI value as 45 13 , this is frequently used 17 , 38 . However, the researchers chose several cutoff levels according to study design, such as median, tertile, or ROC analysis 15 , 18 , 20 , 39 . In previous studies, the PNI cut-off value for defining undernutrition varied between 45 and 50.…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic nutritional index (PNI), calculated from one’s serum albumin concentration and total lymphocyte count in the peripheral blood, was developed by Onodera 13 to determine the nutritional and inflammatory status of surgical patients. PNI is a simple indicator used not only in postoperative outcomes in patients but also in evaluating the nutritional status of patients with malignancies 14 , 15 , pulmonary 16 , 17 , heart 18 , 19 , and kidney diseases 20 . However, the prognostic value of PNI in CA-AKI and patient mortality after PCI have not yet been validated.…”
Section: Introductionmentioning
confidence: 99%
“…PNI was initially developed to evaluate preoperative nutritional conditions and surgical complications in patients with gastrointestinal cancers [ 6 ]. Recently, it has been described as an accurate and independent prognostic predictor in human cancers [ 7 10 ], chronic kidney and heart disease [ 11 , 12 ], and autoimmune disease [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, patients in the CCU are often in a heightened proinflammatory state, which can significantly worsen nutritional status ( 34 ), and AKI is known to be associated with intrarenal and systemic inflammation ( 35 ). Consequently, PNI, combined serum albumin and total lymphocyte count, which represent nutritional status and chronic inflammation ( 36 , 37 ), may be indicated for risk stratification and clinical management for patients in the CCU. In the present study, it was demonstrated that PNI, which is clinically and easily available, was an independent predictor for the development of AKI and prognosis in patients in the CCU.…”
Section: Discussionmentioning
confidence: 99%